2020
DOI: 10.1177/1750481320910523
|View full text |Cite
|
Sign up to set email alerts
|

Sensory communication in YouTube reviews: The interactional construction of products

Abstract: This study draws on interactionist frameworks of sensorial communication to analyse product reviews on YouTube. Existing studies of YouTube review work have focused on how vloggers manage conflicting neoliberal identity discourses such as ‘authenticity’, ‘being entertaining’ and ‘selling’. I argue that this focus has been at the expense of the communicative work involved in constructing products in reviews, and I suggest that identity issues should be conceptually expanded through a much broader focus on commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The results could provide a better idea of how consumers act when they watch YouTube product reviews in the context of social commerce. 13 Human Behavior and Emerging Technologies Second, sensory marketing is an essential component of consumer behavior research, because it can provide insight for scholars to understand consumers' perceptions, judgments, and behaviors [30]. In this study, sensory marketing was used to explore how visual and auditory cues in You-Tube product reviews may impact parasocial interactions with YouTubers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results could provide a better idea of how consumers act when they watch YouTube product reviews in the context of social commerce. 13 Human Behavior and Emerging Technologies Second, sensory marketing is an essential component of consumer behavior research, because it can provide insight for scholars to understand consumers' perceptions, judgments, and behaviors [30]. In this study, sensory marketing was used to explore how visual and auditory cues in You-Tube product reviews may impact parasocial interactions with YouTubers.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study focused on the visual and auditory cues within product review videos. Previous studies have revealed numerous details regarding the visual and auditory cues in YouTube product reviews, including those related to product appearance, design, colour, YouTuber gestures, background music, and descriptive language [3,13,15]. Consequently, through the sensory cues for the products demonstrated by YouTubers, consumers gain experience with the product, which will bring them into evaluation development of the product's virtual sensory experience and convert sensory information into decision-making stages.…”
Section: Sensory Marketing In Youtube Productmentioning
confidence: 99%
See 2 more Smart Citations